Television advertisements for high-sugar foods and beverages: effect on children's snack food intake. Issue 5 (14th March 2021) - Kearney, Justin; Fitzgerald, Rhian; Burnside, Girvan; Higham, Susan; Flannigan, Norah; Halford, Jason C.G.; Boyland, Emma J.
Abstract: Energy-dense food advertising affects children's eating behaviour. However, the impact of high-sugar food advertising specifically on the intake of sweet foods is underexplored. This study sought to determine whether children would increase their intake of sugar and total energy following high-sugar food advertising (relative to toy advertising) and whether dental health, weight status and socio-economic status (SES) would moderate any effect. In a crossover, randomised controlled trial, 101 UK children (forty male) aged 8–10 years were exposed to high-sugar food/beverage and toy advertisements embedded within a cartoon. Their subsequent intake of snack foods and beverages varying in sugar content was measured. A dental examination was performed, and height and weight measurements were taken. Home postcode provided by parents was used to assign participants to SES quintiles. Children consumed a significantly greater amount of energy (203·3 (95 % CI 56·5, 350·2) kJ (48·6 (95 % CI 13·5, 83·7) kcal); P = 0·007) and sugar (6·0 (95 % CI 1·3, 10·7) g; P = 0·012) following food advertisements compared with after toy advertisements. This was driven by increased intake of the items with most sugar (chocolate and jelly sweets). Children of healthy weight and with dental caries had the greatest intake response to food advertising exposure, but there were no differences by SES. Acute experimental food advertising exposure increases food intake in children. Specifically, high-sugar food and beverage advertising promotes the consumption of high-sugar food items. The debate around the negative health effects of food advertising on children should be widened to include dental health as well as overall dietary health and obesity.